A simple active carbody roll scheme for hydraulically actuated railway vehicles using internal model control. (January 2022) - Di Gialleonardo, Egidio; Santelia, Matteo; Bruni, Stefano; Zolotas, Argyrios
Abstract: The paper presents the first classical internal model control (IMC) design in the context of railway carbody roll control. We propose a simple control approach for a recent hydraulically actuated vehicle body roll concept that offers limited carbody roll. The IMC approach addresses both preview- and nulling-type tilt setups, highlighting related benefits and limitations. The design provides a model simplification process that facilitates PI and PID-type control structures without the need for complex optimization. A simple, yet practical, tool for the industrial rail rolling stock engineer in vehicle control design is offered. Vehicle roll performance is rigorously studied on the deterministic (curving acceleration response) and stochastic (ride quality) trade off. Simulations are performed on an in-house multibody dynamics software package employing a realistic nonlinear railway vehicle model and allow to appropriately assess the performance of preview and nulling type tilt performance. The results obtained confirm that preview tilt control offers the better tilt performance as it utilizes a tilt command reference, and highlighted that nulling-type tilt performance remains at a relatively comparable level with the former. Graphical abstract: Highlights: The first Internal Model Control design related to railway carbody roll is presented. A simple control design, for carbody roll with hydraulic actuation, is proposed. The control design provides a model simplification process. PI/PID-type control structures without adopting complex optimization are designed. Performance of preview and nulling-type tilt setups are compared. Vehicle roll performance is studied on the deterministic and stochastic trade off.